The opinions of postgraduate nursing students about evidence-based practice: A qualitative study - (:unkn) unknown (My University, 2023)
Objective: This study was conducted for the purpose of exploring the opinions and experiences of postgraduate nursing students regarding evidence-based practice and its use in the clinical setting in Turkey. Methods: A qualitative study design was employed. Data in this research study were collected through Semi-structured questions were asked face-to-face in focus group discussions. Results: The findings of the study set forth the individual and organizational barriers that faced postgraduate nursing students in their efforts to implement evidence-based practices. The main themes of the study were highlighted as: perceptions regarding evidence-based practice, the impact on the group cared for, challenges faced in the implementation, institutional support in applying practices. Subthemes were data verification, useful and reliable application, difficulties in communicating with colleagues, traditional views, troubles with team collaboration, the indifference of young colleagues, insufficient resources, and the need for a mentor in the workplace. Conclusion: The students in their undergraduate programs, and elective courses on EBP should be added to the curriculum. In order to eliminate organizational barriers, institutions should establish EBP committee and mentoring system.
Keywords: Sağlık Bilimleri; Health Sciences; Klinik Tıp (MED); Clinical Medicine (MED); Evidence-based practice; nursing students; qualitative research